Physical insight on mechanism of photoinduced charge transfer in multipolar photoactive molecules - Yuanzuo Li (2018)
© 2018 The Author(s). Two series of novel dyes were designed based on the multipolar structures of the red dye D35 and blue dye DB, by introducing the furan (F), benzene ring (B) and benzo[c]thiophene (BT) groups into the conjugated bridge of D35 in proper order and adjusting the position of diketopyrrolopyrrole(DPP) unit and the incorporation of fluorine in the conjugated bridge of DB, respectively. We performed the quantum chemistry calculation to investigate the ground state and excited properties in a direct correlation with the spectra properties and abilities of losing or accepting electron for the original and designed molecules. Furthermore, the absorption spectra characteristics in consideration of the aggregation of dyes on the TiO2layer and intermolecular charge transfer rate of the dimers were calculated. The obtained results indicate that the larger intermolecular charge transfer rate leads to the poor photoelectrical properties of the dyes, and the designed dyes D35-3 and DB-2 would exhibit the best photoelectrical properties among the investigated dyes due to their lower energy gaps, widened absorption spectra and prominent charge transfer properties.